Temporal Forecast of Maize Production in Tanzania: An Autoregressive Integrated Moving Average Approach - Maiga, Yohana (Journal of Agricultural Studies, 2024)
This paper aims to model and forecast maize production in Tanzania, emphasizing its crucial contribution to the agricultural sector. Utilizing secondary data on annual maize production in Tanzania from 1961 to 2021, measured in tonnes and sourced from the FAO database, the study employs statistical techniques such as unit root tests, the ARIMA model, and the Ljung-Box test for a comprehensive analysis. The optimal model for forecasting maize production in Tanzania is identified as ARIMA (5,1,5), and the adequacy assessment confirms its effectiveness in predicting maize production values. The ten-year forecast reveals an intermittent pattern, offering valuable insights into anticipated trends. While not explicitly developing an existing theory, this research enhances the understanding of maize production dynamics in Tanzania through the application of advanced statistical methods. Policymakers, agricultural stakeholders, and researchers can leverage these findings to enhance agricultural productivity and food security in Tanzania.